Association between longer hospitalization and development of de novo donor specific antibodies in simultaneous liver–kidney transplant recipients. Issue 1 (1st January 2020) - Yazawa, Masahiko; Cseprekal, Orsolya; Helmick, Ryan A.; Talwar, Manish; Balaraman, Vasanthi; Podila, Pradeep S. B.; Fossey, Sallyanne; Satapathy, Sanjaya K.; Eason, James D.; Molnar, Miklos Z.
Abstract: Background: De novo Donor Specific Antibodies (DSA) are considered as a risk factor for the kidney allograft outcomes in recipients after simultaneous liver–kidney transplantation (SLKT). We hypothesized that length of hospital stay (LOS) might be associated with de novo DSA development of due to the increased likelihood of receiving blood transfusions with reduced immunosuppressive regimens. Methods: This study is a single-center, retrospective cohort study consisting of 85 recipients who underwent SLKT from 2009 to 2018 in our hospital. We divided the patients into two groups according to LOS [long hospital stay (L) group (LOS >14 days) and short hospital stay (S) group (LOS ≤14 days)]. Propensity score (PS) has been created using logistic regression to predict LOS greater than median of 14 days. The association between the presence of de novo DSA and LOS was assessed by logistic regression models adjusted for PS. Results: The mean age at transplantation of the entire cohort was 55.5 ± 10.1 years. Sixty percent of the recipients were male and Caucasian. Median LOS in (L) group was three-fold longer than (S) group [L: median 30 days (IQR: 21–52), S: median 8.5 days (IQR: 7–11)]. Eight patients developed de novo DSA after SLKT (9.4%), all of them were in (L) group. Longer LOS was significantly associated with higher risk of development of de novo DSA in unadjusted (OR+ each 5 days : 1.09, 95% CI:1.02–1.16) and PS adjusted (OR+ each 5 days : 1.11, 95% CI:1.02–1.21) analysis. Conclusion: Longer hospitalization is significantly associated with the development of de novo DSA in SLKT.